Essays on cooperation, migration and trust - Marino Fages, Diego (2023)
This dissertation presents three studies related to cooperation, trust and social preferences. It can be summarized in two main topics, namely, cultural assimilation and cooperation in public good games. The first two studies explore how migrants assimilate in their social preferences towards those that are prevalent in their host place. The first study refers to an international context and focuses on altruism, positive and negative reciprocity and trust. The second study focuses on internal migrants in Switzerland and how they assimilate in their trust on strangers. I find evidence of a causal relationship in line with the assimilation hypothesis. The last study focuses on cooperation in social dilemmas. Here I explore how people respond in terms of beliefs, preferences and behaviour when they participate in public good games in groups of different sizes. For this, I develop a new version of the strategy method and conduct an online experiment with different parameters. I find the preferences to be rather stable with a stronger effect on beliefs. Finally, I find some evidence of a negative effect of group size on contributions.